A sclerochronological archive for Antarctic coastal waters based on the marine bivalve Yoldia eightsi (Jay, 1839) from the South Orkney Islands. (February 2017) - Román-González, Alejandro; Scourse, James D; Richardson, Christopher A; Peck, Lloyd S; Bentley, Michael J; Butler, Paul G
The scarcity of long instrumental series from the Southern Ocean limits our understanding of key climate and environmental feedbacks within the Antarctic system. We present an assessment for the Antarctic mollusc bivalve Yoldia eightsi as an Antarctic coastal climatological archive, based on annually-resolved growth pattern of 20 live-collected specimens in 1988 from Factory Cove, Signy Island (South Orkney Islands). Two detrending methods were applied to the growth increment series: negative exponential detrending and regional curve standardization (RCS) detrending. The RCS-chronology showed consistent synchronous growth in the population for a 20 year period (1968-1988; expressed population signal ⩾ 0.85), a negative correlation between the RCS-chronology and the fast-ice duration record (r= -0.41, N= 24, P⩽ 0.05) and winter duration (r= -0.52, N=24, P⩽ 0.01) and positive correlations with mean winter sea surface temperature (SST; r= 0.57, N= 24, P⩽ 0.01), mean summer SST (r= 0.46, N= 24, P⩽ 0.05) and mean annual SST (r= 0.48, N= 24, P⩽ 0.05). The chronology appears to record the environmental conditions generated during the Weddell Polynya event (1973 -1976) as detectable abrupt changes in the annual growth patterns. Over eight years (1973-1980) a negative relationship between shell growth and suspended chlorophyll (i.e. a proxy for surface productivity) is apparent which is likely influenced by the seasonal deposition of organic phytodetritus on the seabed following surface water phytoplankton blooms. Our results form a basis for establishing Y. eightsi as an environmental archive for coastal Antarctic waters.